PENGEMBANGAN INSTRUMEN KETERAMPILAN BERPIKIR KRITIS PADA PEMBELAJARAN PPKN SD - Linda Zakiah (Jurnal Pendidikan Dasar, 2020)
Abstract: Higher-order thinking skills are skills that are needed by students to become a superior generation in global competition in the present and the future. Civic Education is one that requires students to have critical thinking skills. The purpose of this study was to produce valid and reliable instruments for critical thinking skills in Civic Education. This research is a type of Research and Development (R&D). The subjects of the media product trial assessment instrument form oriented critical thinking skills with Civic Education material were 30 students of grade V. Therefore, researchers are interested in developing critical thinking skills instruments in Civic Education. This instrument refers to the assessment of students' critical thinking skills in primary school accordance with the objectives of Civic Education. By using this instrument the teacher can develop critical thinking skills in every Civic Education lesson in the classroom. The results of the development of critical thinking skills instruments that are made can be used by teachers as a tool to develop students' thinking skills in Civic Education.